ANALISIS KUMPULAN PUISI “99 UNTUK TUHANKU” KARYA EMHA AINUN NADJIB: KAJIAN MIMETIK - M. Chillah Syarifah Sakinah; Tri Indrayanti (Universitas PGRI Adi Buana Surabaya, 2019)
The view of this mimetic approach is the assumption that poetry is an imitation of nature or depiction of the world and human life in the universe. the target studied is the extent to which poetry represents the real world or the universe and the possibility of intellectuality with other works. the relationship between reality and imagery in literature is a dialectical relationship. mimetic is not possible without creation, but creation is not possible without mimetics. doses and links between the two can differ in culture, time, literature, personality of the author, etc. but one without the other is impossible and lastly the combination of creation and mimetics is not only valid and true for literary writers. Giving meaning to literature is an endless journey between two realities and an imaginary world. Literary works that are released and reality lose something essential, that is, the involvement of the reader in existence as a human being. Literary readers who lose the power of imagination exclude things that are no less essential for humans, namely alternatives to existence that exist with all their deficiencies or simpler thanks to art, literature, especially humans can live in a combination of reality and dreams that are both for us as humans.